Formation of Tolerance at School Pupils Based on the Use of National Traditions - Raushan Mamadiyarovna, Medetova (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of to develop the basis for the formation of tolerance among schoolchildren based on the use of national traditions in the educational process of the comprehensive school. The following tasks are defined in the article as: to analyze the level of formation of tolerance among schoolchildren in the process of studying materials of folk pedagogy; to develop components for the formation of tolerance in students of grades 1-9 of secondary schools; to formulate the conceptual basis for the formation of tolerance among students in grades 1–9 of secondary schools; to improve the locally-modular educational technology for the formation of tolerance among schoolchildren based on the use of national traditions in the educational process of the school; to create a model for the formation of tolerance among students in grades 1–9 of secondary schools based on the invaluable experience of the people, who embodied in their traditions openness, friendliness, sincerity, and other universal values. The article consists of from introduction, literature survey, methodology, recommendation, discussions, and conclusion.